Optimasi Pengukuran Dinamis dari Visualisasi Model Ruangan 3D Menggunakan Sensor LiDAR dan Framework RoomPlan - Mulyana, Dadang Iskandar; Pratiwi, Tiyas Aria (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Utilizing limited space to be more functional and aesthetic, such as adding furniture or using it as gardening space, can be achieved through effective room mapping. However, manual mapping methods have limitations such as inaccurate measurements, time efficiency, and also lack of room visualization. In this modern era, robotics technology has been widely applied in everyday life, one of which is the use of LiDAR sensors for room mapping. This paper discusses a room mapping system using a mobile application that utilizes LiDAR sensors. The mapping process is carried out by scanning the area to be mapped and rotating the area 360 degrees. The result of this mapping is a scanned 3D model of the room, which allows measurements from every side of the room. Research shows that the mapping results from the software created are similar in shape to actual field conditions. In addition, the measurement accuracy only has a small difference of 0.2%. It is hoped that this research can make it easier for humans to map rooms and make better use of limited space.